Pentingnya Inovasi Pendidikan Dalam Meningkatkan Profesionalisme Tenaga Kependidikan Anak Usia Dini (PAUD) - Siske Fonike Pello; Marisa Aulia Gea (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
This study examines the influence of innovation in early childhood education on improving the professionalism of educators, because early childhood education is a critical stage in child development where educators have an important role in providing quality educational experiences, innovation in the context of early childhood education using technology, new learning methods and teaching strategies provided by educators creatively and also improvements to The curriculum used because this study involves field research that collects data through interviews, surveys and data analysis through documents because the results of the study show that educational innovations in early childhood education can improve the professionalism of education personnel by using technology and more modern learning methods, education personnel can be more effective in managing the learning environment that occurs in children Early and also look at the cognitive and social development of children and also education staff in collaboration with the parents of each student. And educational innovation also has a good impact on the motivation of education personnel to improve the quality possessed by each education staff through training and also development that can be done by education personnel with the results of this study showing that the rocks given in educational innovation can be carried out. Being an effective way to improve the professionalism of early childhood education personnel which will ultimately contribute to improving the quality of early childhood education as a whole in an era that continues to change and also develop, so we can see that innovation is the first key to improving early childhood education and the professionalism of education personnel involved in early childhood education institutions.